The invisible Threat: Assessing the reproductive and transgenerational impacts of micro- and nanoplastics on fish - Yi, Jia; Ma, Yilei; Ruan, Jing; You, Si; Ma, Jiahui; Yu, Haiyang; Zhao, Jing; Zhang, Kun; Yang, Qinsi; Jin, Libo; Zeng, Guoming; Sun, Da (Environment international, 2024)
[Display omitted] •MNPs affect fish reproduction under isolated and combined pollution exposures.•The risk of MNPs causing heritable toxic effects in fish offspring is highlighted.•Gonadal damage and hormonal disruption are two biological pathways affected by MNPs.•Points out research gaps in understanding MNPs' size-specific and long-term effects.•Assessing MNP ecological risks is crucial to protecting aquatic life. Micro- and nanoplastics (MNPs), emerging as pervasive environmental pollutants, present multifaceted threats to diverse ecosystems. This review critically examines the ability of MNPs to traverse biological barriers in fish, leading to their accumulation in gonadal tissues and subsequent reproductive toxicity. A focal concern is the potential transgenerational harm, where offspring not directly exposed to MNPs exhibit toxic effects. Characterized by extensive specific surface areas and marked surface hydrophobicity, MNPs readily adsorb and concentrate other environmental contaminants, potentially intensifying reproductive and transgenerational toxicity. This comprehensive analysis aims to provide profound insights into the repercussions of MNPs on fish reproductive health and progeny, highlighting the intricate interplay between MNPs and other pollutants. We delve into the mechanisms of MNPs-induced reproductive toxicity, including gonadal histopathologic alterations, oxidative stress, and disruptions in the hypothalamic-pituitary–gonadal axis. The review also underscores the urgency for future research to explore the size-specific toxic dynamics of MNPs and the long-term implications of chronic exposure. Understanding these aspects is crucial for assessing the ecological risks posed by MNPs and formulating strategies to safeguard aquatic life.